The use of contrast enhancement in the diagnosis of simple and complex cysts kidneys - Ya. A. Soloviev; L. A. Mitina; B. Ya. Alekseev; S. O. Stepanov; A. S. Kalpinskiy; O. V. Dimitrov; E. A. Nazoikin (Biomedical Photonics, 2020)
In developed countries, the main methods of research and dynamic monitoring of cystic kidney formations are CT and MRI, but their use is impossible in patients with severe concomitant diseases, as well as in the presence of metal structures, pacemakers, etc. Additionally, taking into account the high dose of radiation exposure when using CT obtained by the patient during dynamic observation, the development of alternative methods is relevant. These include, but not limited to, ultrasound using contrast enhancement, which can be used as an alternative or additional method in primary diagnosis or in the dynamic observation of cystic kidney formations. In the article, the authors provide their own experience with the use of an ultrasound contrast medium for the diagnosis and dynamic observation of complex kidney cysts, as well as the introduction of ultrasound observation using a contrast medium to classify patients according to Bosniak M.A.The study included the results of the use of contrast enhanced ultrasound (CEUS) in 28 patients with various cystic formations of the kidneys. The patients were previously divided into two groups: the first consisted of 13 patients with simple cysts, the second – 15 with suspected complex cysts. As a result of the study, the patients were distributed as follows: 15 patients were classified as Bosniak type I, 7 patients – as type II, 3 - type III, 3 - type IV. The studied CEUS method is simple and effective. The specificity of the method was 78.57%, the accuracy of the method was 85.71%, the predictive value of the positive result was 81.25%, and the predictive value of the negative result was 91.66%. CEUS helps to quickly and accurately conduct differential diagnosis between a simple cyst and a complex one, as well as classify cysts according to M.A. Bosniak.